Factors that contribute to job stress among employees at Scomi Oiltools Sdn Bhd / Norhaslinda Aziz - Aziz, Norhaslinda (Faculty of Business and Management, 2013)
Job stress is a common problem that faced by employees in any organization. With the fast pace business environment, job stress is an unavoidable situation that employees have to face. When employees cannot cope with the stress at work, it could result to employee turnover, absenteeism, reduce in job performance and also their motivation to perform job. There are many factors that could lead to job stress among the employees such as role ambiguity, working environment, politics in office, leadership, reward offered and many more. As for this research which was conducted at Scomi Oiltools Sdn Bhd, the researcher focused on three factors which are leadership styles, individual and working environment. The first objective of this research is to identify the relationship between leadership styles and job stress. The second objective is to identify the relationship between individual and job stress and last objective is to identify the relationship between working environment and job stress. The total numbers of respondents are 56 people who are selected from the company through Simple Random Sampling. The data were collected through distribution of questionnaire and was interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation Analysis. 56 sets of questionnaires were distributed to the respondents. The findings supported all of the objectives where there is relationship between the independent variables which are leadership styles, individual and working environment with job stress.